Disseminated paracoccidioidomycosis under biological therapy - Jaime A Ibarra-Burgos; Simón Correa-Sierra; Sergio A Londoño-Tabares (Journal of Infection in Developing Countries, 2025)
Introduction: Paracoccidioidomycosis is an endemic mycotic infection caused by Paracoccidioides spp., prevalent in Central and South American countries. Anti-tumor necrosis factor (TNF) alpha agents, commonly used for autoimmune diseases, increase the risk of severe infections. We present a case of anti-TNF alpha-related paracoccidioidomycosis in a 71-year-old male farmer from Colombia.